2007
DOI: 10.1590/s0100-83582007000300019
|View full text |Cite
|
Sign up to set email alerts
|

Controle químico de brilhantina (Pilea microphylla) no cultivo de orquídeas

Abstract: RESUMO -Este trabalho teve como objetivo avaliar a eficácia do oxyfluorfen no controle da brilhantina (Pilea microphylla) em cultivo de orquídeas. Foram realizados dois experimentos, no delineamento de blocos ao acaso, no esquema fatorial 2 x 7, com três repetições. Um dos experimentos foi constituído por duas espécies de orquídeas (Epidendrum ibaguensis e Dendrobium sp.) e sete doses de oxyfluorfen (0,000, 0,024, 0,072, 0,144, 0,216, 0,288 e 0,36 L ha -1 do i.a.), pulverizadas em área total, e o outro, pelas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
7
0
2
Order By: Relevance
“…In another study, Freitas et al (2007a) found that oxyfluorfen was selective to Epidendrum ibaguensis and Dendrobium sp. orchids and provided efficient control of P. microphylla, above 90% at 30 DAA, for more than 62.4 g ha -1…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In another study, Freitas et al (2007a) found that oxyfluorfen was selective to Epidendrum ibaguensis and Dendrobium sp. orchids and provided efficient control of P. microphylla, above 90% at 30 DAA, for more than 62.4 g ha -1…”
Section: Resultsmentioning
confidence: 96%
“…Amongall ornamental plants marketed, the ones from the orchid family deserve prominent role, due to its high acceptance and exuberance of its flowers (Freitas et al, 2007a), as well as showing great adaptability to various environments (Paula & Silva, 2006). For commercial cultivation, using quality substrate, which supports the development of these flowering, becomes extremely important (Assis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Both herbicides (oxyfluorfen and flumioxazin) molecules are absorbed by leaves and the roots, and have great persistence in soil, increasing and prolonging its effect (Jursík et al, 2011;Jung, 2011), justifying the results observed in this test. Freitas et al (2007a), found selectivity of oxyfluorfen molecule for orchids Epidendrum ibaguensis and Dendrobium sp., providing effective control (above 90%) of P. microphylla at 30 DAA, for doses 62.4g ha -1 a.i. and/or superior.…”
Section: Resultsmentioning
confidence: 98%
“…Among the ornamental plants marketed, there are the members of the family Orchideaceae, with wide acceptance due to the exuberance of its flowers (Freitas et al, 2007a), and considerable adaptive ability to more distinct environments (Paula and Silva, 2006). According to Thomas and Michael (2007), orchids have floral characteristics portrayed through wide range of shapes, sizes and color, and their species or hybrids are highly valued for ornamental trade, either pot or cutting.…”
Section: Introductionmentioning
confidence: 99%
“…Rosa (2007) afirma que os efeitos observados por ação tóxica de oxyfluorfen consistem na descoloração (clorose) e no crescimento anormal das folhas. Resultados que demonstram o efeito fitotóxico do oxyfluorfen aplicado em pós-emergência diretamente sobre as plantas foram observados por Ronchi & Silva (2003) em mudas de café; por Freitas et al (2007a), em plantas ornamentais; e por Pivetta et al (2008), em mudas de sálvia (Salvia splendens). Contudo, em aplicação dirigida, Freitas et al (2007a,b) não observaram sintomas tóxicos em nenhuma espécie ornamental estudada.…”
Section: Resultsunclassified